Understanding Cultural Differences in Hospitality Students’ Acceptance of Service Robots: A Cross-National Study in Portugal, Brazil and Greece - Rodrigues, Rosa; Palrão, Teresa; Madeira, Arlindo; Apostolakis, Alexandros (Journal of Cultural Analysis and Social Change, 2025)
This study explores how cultural differences influence hospitality students’ acceptance of service robots and their intention to work in partially robotized environments. Building on the Technology Acceptance Model (TAM), the Theory of Planned Behavior (TPB) and Hofstede’s cultural dimensions, this cross-national study compares the perceptions of 532 hospitality and tourism students from Portugal, Brazil, and Greece. Using multivariate analysis (MANOVA) and multi-group structural equation modelling (MGSEM), the findings reveal significant differences across countries. Greek students express the highest willingness to work with robots, while Portuguese students report stronger attachment to traditional hospitality values. Although culture significantly influences students’ views on hospitality and robot use, it does not directly predict their intention to work in robotized environments—suggesting other factors mediate this relationship. The study highlights the importance of embedding technological competencies and emotional intelligence in hospitality education, while offering practical guidance for AI developers and human–robot interaction (HRI) designers. These findings contribute to cross-cultural research on service robot acceptance and provide actionable insights for preparing the future workforce in the context of hospitality automation.